Hearts of Darkness: the experience of horror in Roger Casement's writings - the fabrication of an anti-hero - Roberto Carlos de Andrade (Ilha do Desterro)
The article presents an analysis of texts by a multitude of authors who deal with Roger Casement’s writings, aiming at assessing how those authors fabricate a discourse based on alleged acts in order to perpetuate a representation of Casement’s persona. Casement ends up being both a hero – up until his arrest and condemnation as a traitor to the British Empire – and an antihero – not only after his arrest but also and specially after his Black diaries were uncovered, bringing about Casement’s disappearance from the public’s view as an important humanist and character in British and Irish histories. The article also tackles the close relation between Casement and the main characters in Joseph Conrad’s Heart of Darkness.